Bachelor of Applied Arts with Honours (Design Technology) - Universiti Malaysia Sarawak, Faculty of Applied and Creative Arts (Universiti Malaysia Sarawak, (UNIMAS), 2022)
Sijil Sarjana Muda Fakulti Seni Gunaan dan Kreatif 2022 bagi 71 orang pelajar.